Bilateral and anterior-posterior muscular imbalances in swimmers - Becker, T.; Havriluk, R. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to determine the relative magnitude of bilateral and anterior-posterior differences in swimmers. Peak band force was measured during aquatic exercise (horizontal arm abduction and adduction in a Standing position) and swimming (freestyle and backstroke). The peak force values were significantly higher (p<.01) for exercise adduction than abduction and for the swim stroke with the arm in the adducted position (freestyle) rather than the abducted position (backstroke) . The magnitude of the anterior-posterior difference was large for both exercise (1.5o) and swimming (.8o). Bilateral differences were trivial (.1o, ns) in comparison. A training regimen that strengthens the arm abductors may not only decrease the incidence of injuries in all four strokes, but also increase hand force and, therefore, improve performance in backstroke.